2012
DOI: 10.14411/eje.2012.069
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification and microhabitat selection by the Great Capricorn Beetle (Cerambyx cerdo) (Coleoptera: Cerambycidae) in open-grown, veteran oaks

Abstract: Abstract. The great capricorn beetle or Cerambyx longicorn (Cerambyx cerdo, Linnaeus, 1758) is an internationally protected umbrella species representing the highly diverse and endangered fauna associated with senescent oaks. For the conservation and monitoring of populations of C. cerdo it is important to have a good knowledge of its microhabitat requirements. We investigated determinants and patterns of C. cerdo distribution within individual old, open-grown oaks. Trees inhabited by this species were climbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 33 publications
2
52
0
16
Order By: Relevance
“…The physiological condition of the tree plays a decisive role in the settlement of great capricorn beetle (Rudnev 1957;Albert et al 2012). Our research also showed that the determining criterion for settlement of great capricorn beetle is the sanitary condition of trees, and the more weakened trees are more suitable for settlement and development of C. cerdo.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…The physiological condition of the tree plays a decisive role in the settlement of great capricorn beetle (Rudnev 1957;Albert et al 2012). Our research also showed that the determining criterion for settlement of great capricorn beetle is the sanitary condition of trees, and the more weakened trees are more suitable for settlement and development of C. cerdo.…”
Section: Discussionsupporting
confidence: 52%
“…The presence of a significant number of older trees damaged by root rot and other factors is a prerequisite for long-term existence of mass reproduction of C. cerdo. Albert et al (2012) indicates the strong relationship between the diameter of tree and the number of fly holes on the tree. Also, this study revealed that the number of exit holes in the trunks of large, open-grown oaks was positively associated with the diameter of the trunk and openness and negatively with height above the ground, and the effects of diameter and openness changed with height (Albert et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations